Studies on Growth, Yield and Quality of Garlic (Allium sativum L.) as Affected by Herbicides and Weeds - Patil, Badri Vishal; Naruka, I. S.; Shaktawat, R. P. S.; Verma, K. S. (International Journal of Bio-resource and Stress Management, 2016)
A field experiment was conducted at the research farm, College of Horticulture, Mandsaur (Madhya Pradesh), India during the rabi, 2012−13 to study the effect of different herbicides on weed and performance of garlic (Allium sativum L.). There were ten treatments in the experiment consisted of cultural methods and different herbicides and their doses. The different treatments significantly influenced the growth, yield and quality attributes of garlic. Significant maximum plant height, number of leaves plant-1, chlorophyll content in leaves, leaf area plant-1, TSS content of bulb (%), volatile oil content in bulb (%), neck thickness, number of cloves bulb-1, fresh and dry weight of 20 cloves, pollar and equatorial diameter of bulb, fresh and dry weight of bulb and bulb yield were recorded with weed free treatment followed by oxyfluorfen 23.5% EC @ 1.0 l ha-1 and oxadiargyl 6% EC @ 1.0 l ha-1. Similarly minimum days to maturity, weed population m-2 at 60 and 90 DAS and weed dry matter at harvest was recorded with weed free treatment followed by oxyfluorfen 23.5% EC @ 1.0 l ha-1 and oxadiargyl 6% EC @ 1.0 l ha-1. Among the treatment applied, Oxyfluorfen 23.5% EC @ 1.0 l ha-1, Oxadiargyl 6% EC @ 1.0 l ha-1 and weed free treatment gave significantly highest bulb yield by 125.90, 124.54 and 126.63 q ha-1 which were at par with each other.